IMPROVING EGGS PRODUCTION AND QUALITY FOR LAYER BY STOCKING DENSITY AND MEDICINAL PLANTS - Mustafa, Alaa . A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to increasing egg production by supplementing medicinal plants Salvia officinalis L and Lavandula angustifolia L powders as antistressors in hen layer diet under high stocking density during different conditions. 240 two hundred and forty 31 weeks old hens layer were randomly divided into seven treatments with three replicates in each, reared for 16 weeks as folowings; T0 negative control normal density 24 layers, 8 layers/1.20 m2 in each replicate (7 hens/m2) fed a basal diet. T1 positive control basal diet, T2 basal diet+ 0.7% salvia, T3 basal diet+ 0.9% salvia, T4 basal diet+ 0.7% lavender, T5 basal diet+ 0.9% lavender and T6 basal diet+ 0.7% mix (0.35% salvia+0.35% lavender). From T1-T6, the stock density is 36 layers in each treatments, 12 layers/1.30 m2 (9 hens/m2). All layers were exposed in hot, normal, semi-cold conditions. The results showed productivity, hematology and immunity traits significantly improved by adding the two plants 9% lavender, 0.7% lavender, and 0.7% mixed, respectively, under stocking density led to significantly increase hen day egg production HD%, egg mass g, egg weight g, FCR for feed/1g egg, and feed/1egg were improved by 0.9% lavender and 0.7% mixed. Moreover, egg quality improved by adding the medical herbals. The yolk color was also improved colorful, particularly in 0.9% lavender. Red blood cells RBC 106 cells/mm3, PCV %, HGB g/dL, lymphocyte%, and total protein mg/dL were significantly increased by 0.9% salvia, 0.7% lavender, 0.9% lavender, and 0.7% mixed, while heterophil %,and the stress indicators H/L ratio and glucose mg/dL decreased. It was concluded that it's possible to increase  the number of hens per m2 area to increase number of egg production by supplementing medical herbals salvia and lavender without any adverse effect.